2008
DOI: 10.1371/journal.pone.0001840
|View full text |Cite
|
Sign up to set email alerts
|

Seeing ‘Where’ through the Ears: Effects of Learning-by-Doing and Long-Term Sensory Deprivation on Localization Based on Image-to-Sound Substitution

Abstract: BackgroundSensory substitution devices for the blind translate inaccessible visual information into a format that intact sensory pathways can process. We here tested image-to-sound conversion-based localization of visual stimuli (LEDs and objects) in 13 blindfolded participants.Methods and FindingsSubjects were assigned to different roles as a function of two variables: visual deprivation (blindfolded continuously (Bc) for 24 hours per day for 21 days; blindfolded for the tests only (Bt)) and system use (syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 17 publications
4
64
0
Order By: Relevance
“…In principle, the body part itself versus its mode of exploration could be studied independently (eg by moving the head in a hand-like way and moving the hand in a head-like way). In addition, it is important that future research develops paradigms for assessing localisation of objects with sensory substitution devices using measures of reaching and grasping (eg as in Proulx et al 2008) which may depend less on consciously reportable knowledge of position (eg Goodale and Milner 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the body part itself versus its mode of exploration could be studied independently (eg by moving the head in a hand-like way and moving the hand in a head-like way). In addition, it is important that future research develops paradigms for assessing localisation of objects with sensory substitution devices using measures of reaching and grasping (eg as in Proulx et al 2008) which may depend less on consciously reportable knowledge of position (eg Goodale and Milner 1992).…”
Section: Discussionmentioning
confidence: 99%
“…And, indeed, the idea that the experience of TVSSuse is like vision is supported by evidence for similar perceptual effects, e.g., occlusion and parallax, as well as by verbal reports of some of the participants. In addition, a recent study by Ward and Meijer [53] into the long-term effects of using a related visual-to-sound substitution system the "vOICe," see [38] in blind users has provided strong indications that visual-like experiences are in fact made possible by these kinds of interfaces see also [44].…”
Section: Enactive Interfacesmentioning
confidence: 99%
“…The ability to localize static objects has already been demonstrated (Proulx et al, 2008). Other works have shown that participants are capable of grabbing a distant object (Levy-Tzedek et al, 2012).…”
Section: Introductionmentioning
confidence: 92%